Indications for lung transplant referral and listing - Shweish, Omar; Dronavalli, Goutham (Journal of Thoracic Disease; Vol 11, Supplement 14 (September 29, 2019): Journal of Thoracic Disease (The Advanced Lung Disease: Novel Therapies and Controversies Conference), 2019)
Lung transplantation is a valuable therapeutic option for many patients with severe lung disease who have exhausted other medical or surgical therapies. However, since lungs are not a manufacturable organ like artificial heart valves or left ventricular assist devices, and since they are a limited resource compared to number of patients requiring the organs, the Department of Health and Human Services set the Final Rule of organ allocation in 1998. This led to development and implementation of Lung Allocation Score (LAS) in 2005. The score broadly divides lung diseases into 4 diagnostic criteria with a coefficient factor given to each category. The score is based on the prognostic factors of each patient to determine the risk of mortality without a transplant combined with the probability of patient survival post-transplant. Most of the guidelines for “Indications for referral and listing in lung transplant” is based on consensus opinion as there is limited amount of robust data and trials about this topic. The International Society for Heart and Lung Transplant (ISHLT) has published three editions for candidate selection and listing. In this article, we have attempted to highlight the guidelines and incorporated other disease specific prognostic factors that are not captured in the LAS. Ultimately, there are other factors like geographic location, height, blood group, preformed antibodies, transplant center experience, past wait times and transplant rate, availability of organs, etc., which also play a role especially when considering listing a patient for lung transplant. We also highlighted a representative disease in each category and most criteria for that disease will apply to other diseases in that category. Finally, this article does not delve into the history and reasoning behind each guideline but is meant to provide a general overview of indications and contraindications applicable in the field of adult lung transplantation.